2007
DOI: 10.1103/physrevb.75.041401
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit gap of graphene: First-principles calculations

Abstract: Even though graphene is a low energy system consisting of the two dimensional honeycomb lattice of carbon atoms, its quasi-particle excitations are fully described by the 2+1 dimensional relativistic Dirac equation. In this paper we show that while the spin-orbit interaction in graphene is of the order of $4 meV$, it opens up a gap of the order of $10^{-3} meV$ at the Dirac points. We present the first principle calculation of the spin-orbit gap, and explain the behavior in terms of a simple tight-binding mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
678
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 955 publications
(705 citation statements)
references
References 16 publications
20
678
3
4
Order By: Relevance
“…However, spin lifetimes measured in SLG spin valves are much shorter (0.05 -1.2 ns) 6-9 than predicted (100 ns -1 s) [1][2][3][4][5] . Thus, the origin of spin relaxation in SLG has become a central issue for graphene spintronics and has motivated intense theoretical and experimental studies.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, spin lifetimes measured in SLG spin valves are much shorter (0.05 -1.2 ns) 6-9 than predicted (100 ns -1 s) [1][2][3][4][5] . Thus, the origin of spin relaxation in SLG has become a central issue for graphene spintronics and has motivated intense theoretical and experimental studies.…”
Section: Introductionmentioning
confidence: 85%
“…Single layer graphene (SLG) is a promising material for spintronics due to theoretical predictions of long spin lifetimes based on its low intrinsic spin-orbit and hyperfine couplings [1][2][3][4][5] . However, spin lifetimes measured in SLG spin valves are much shorter (0.05 -1.2 ns) 6-9 than predicted (100 ns -1 s) [1][2][3][4][5] .…”
mentioning
confidence: 99%
“…Graphene has since become a prototypical model system for 2D TIs 1,2 ; however, its bulk energy gap is too small to make the predicted QSH effect observable under normal conditions (a low temperature of below 0.01 K is required) 12 . Several proposals have been put forward to enhance the SOC effect of graphene, such as a direct deposition of hydrogen or heavy element adatoms [8][9][13][14][15] .…”
mentioning
confidence: 99%
“…Subsequent computational work 22,23 showed that the magnitude of the intrinsic spin-orbit coupling in graphene was so small that would render the observation of the QSH phase almost impossible. However, there are graphene-like materials, such as Silicene and other group IV honeycomb crystals, for which the Kane Mele model applies 24 and for which these predictions are relevant.…”
Section: Introductionmentioning
confidence: 99%